Unveiling the mechanism of Pogostemon cablin (Blanco) Benth in treating heat illnesses via network pharmacology and molecular simulation - Xiang Li; Sishi Jiang; Haili Li; Shilin Li; Yingchun Hu (PLoS ONE, 2025)
Background Heat illness is a dangerous condition marked by a widespread inflammatory response. Although Pogostemon cablin (Blanco) Benth and its derivatives are clinically used, their mechanisms remain unclear. Methods 11 heat illness patients and 14 healthy volunteers from Southwest Medical University Affiliated Hospital were enrolled. Bulk RNA sequencing of peripheral blood samples identified disease-relevant modules via weighted gene co-expression network analysis (WGCNA). Active ingredients and targets of P. cablin were retrieved from TCMSP. GO/KEGG, protein-protein interaction (PPI), and ROC analyses were performed. Core genes were localized through single-cell RNA sequencing, with compound-target interactions validated by molecular docking. Results Enrichment analysis revealed nine cross-targets in TNF/NF-κB pathways. Core targets (NFKBIA, PARP1) showed high diagnostic sensitivity/specificity. Single-cell data indicated predominant expression in monocytes and CD1C-CD141 dendritic cells. Molecular docking demonstrated strong affinity of quercetin/quercimeritrin for NFKBIA/PARP1/LACTB, with molecular dynamics confirming structural stability of complexes (RMSD < 2Å after 100 ns). Conclusion This pioneering study integrates network pharmacology and molecular simulations to elucidate P. cablin’s therapeutic targets for heat illness, providing a foundation for advanced therapies.